The reliability of 4-minute and 20-minute time trials and their relationships to functional threshold power in trained cyclists - MacInnis, M. J.; Thomas, A. C. Q.; Phillips, S. M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: The mean power output (MPO) from a 60-min time trial (TT)-also known as functional threshold power, or FTP-is a standard measure of cycling performance; however, shorter performance tests are desirable to reduce the burden of performance testing. The authors sought to determine the reliability of 4- and 20-min TTs and the extent to which these short TTs were associated with 60-min MPO. Methods: Trained male cyclists (n = 8; age = 25 [5] y; VO2max = 71 [5] mL/kg/min) performed two 4-min TTs, two 20-min TTs, and one 60-min TT. Critical power (CP) was estimated from 4- and 20-min TTs. The typical error of the mean (TEM) and intraclass correlation coefficient (ICC) were calculated to assess reliability, and R2 values were calculated to assess relationships with 60-min MPO. Results: Pairs of 4-min TTs (mean: 417 [SD: 45] W vs 412 [49] W, P = .25; TEM = 8.1 W; ICC = .98), 20-min TTs (342 [36] W vs 344 [33] W, P = .41; TEM = 4.6 W; ICC = .99), and CP estimates (323 [35] W vs 328 [32] W, P = .25; TEM = 6.5; ICC = .98) were reliable. The 4-min MPO (R2 = .95), 20-min MPO (R2 = .92), estimated CP (R2 = .82), and combination of the 4- and 20-min MPO (adjusted R2 = .98) were strongly associated with the 60-min MPO (309 [26] W). Conclusion: The 4- and 20-min TTs appear useful for assessing performance in trained, if not elite, cyclists.